KARO DIALECTAL VARIATION IN TANAH KARO: A LEXICAL AND PHONOLOGICAL SOCIOLINGUISTIC ANALYSIS - Br Sembiring, Sukutenta; Barus, Efendi; Ezir, Ely (JOURNAL OF LANGUAGE, 2025)
Language holds the memory of a community and shapes how people understand themselves, their landscape, and their cultural belonging. This study investigates dialectal variation in the Karo language of Tanah Karo, North Sumatra, through a lexical and phonological sociolinguistic framework. Using a descriptive qualitative design supported by dialectological procedures, the research analyzes 200 Swadesh-based lexical items and natural speech data collected from six native speakers representing three major dialect regions: Julu (Tigapanah), Teruh Deleng (Tiganderket), and Singalor Lau (Tigabinanga). Structured interviews, direct observation, and audio-recorded elicitation sessions formed the basis of the dataset. Findings show that while the dialects remain mutually intelligible, they exhibit systematic micro-variations in vowel realization, lexical selection, and morphophonemic structure. Tigabinanga displays the most consistent vowel fronting and several unique lexical items, whereas Tigapanah and Tiganderket share closer phonological and lexical affinities. These patterns reflect the influence of geographical separation, inter-village communication, and long-standing cultural identity. The study contributes to the documentation of Indonesia’s regional languages and underscores the importance of preserving dialectal diversity. Further research using acoustic phonetics or quantitative dialectometry is recommended to deepen the understanding of phonological distance within the Karo speech community.